The impact of the representatives of three types of process modeling tools on modeler's perceptions and performance. Issue 1 (5th December 2015) - Polančič, Gregor; Jošt, Gregor
Abstract: The quality of process diagrams as well as modelers' performance depends on used modeling tools, which have evolved over past years, also because of changes in software design and architecture. In our research we quantitatively and qualitatively investigated modelers' perceptions and performance when using the representatives of three types of process modeling tools in regard to type of work. A within‐subjects experiment was conducted, where we comparatively observed modelers' perceptions and modeling times when using different modeling tools. For testing the stated hypotheses, the results from 126 experimental participants were analyzed using a one‐way variance analysis. We found that modelers perform their tasks significantly faster with a web tool in case of collaborative work. In addition, we found that participants preferred desktop tool for individual modeling mostly because of its ease of use, whereas in the case of collaborative modeling, participants favored web tool's collaborative functions. Both of them outperformed the representative generic diagraming tool in all given circumstances. The results could be used as guidelines for designing future modeling tools and for modelers who are searching for the most appropriate modeling tools. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The graphical abstract presents the main findings of our research. In respect to individual and collaborative modeling, it highlights the focal modelers' perceptions regarding the acceptance of modeling tools. Additionally, it highlights the preferred architecture of modeling tools (i.e. desktop‐based or web‐based), preferred modeling tools' characteristics and the qualities of modelled diagrams.